DEVELOPING ENGINEERING STUDENTS CRITICAL THINKING FOR PUBLIC SPEAKING THROUGH PROBLEM-BASED LEARNING - Nangimah, Musrifatun (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
Critical thinking skill is crucial for higher education students. However, the development of critical thinking for engineering students has been overlooked. The previous research on students critical thinking in higher education mainly focuses on Humanities and Social Sciences department. Therefore, this research aims to evaluate engineering students critical thinking ability in English public speaking. A case study was carried out on 28 students (18 Males, 8 Females) of Telecommunication Engineering faculty at Institut Teknologi Telkom Purwokerto. The study found that students had the potential to be critical despite their lack of English vocabulary and poor pronunciation ability. They developed critical thinking by understanding the context given, gathering relevant sources as analysis resources, evaluating the gathered information through discussion, and generating the solutions. Evaluative teaching strategies that encourage scaffolding and learning autonomy are needed to enhance their critical thinking.